Phosphorylation Modifications Regulating Cardiac Protein Quality Control Mechanisms - Mishra, Sumita; Dunkerly-Eyring, Brittany L.; Keceli, Gizem; Ranek, Mark J. (Frontiers in Physiology, 2020)
Many forms of cardiac disease, including heart failure, present with inadequate protein quality control. Pathological conditions often involve impaired removal of terminally misfolded proteins. This results in the formation of large protein aggregates, which further reduce cellular viability and cardiac function. Cardiomyocytes have an intricately collaborative protein quality control system to minimize cellular proteotoxicity. Increased expression of chaperones or enhanced clearance of misfolded proteins either by the proteasome or lysosome has been demonstrated to attenuate disease pathogenesis, whereas reduced protein quality control exacerbates pathogenesis. Recent studies have revealed that phosphorylation of key proteins has a potent regulatory role, both promoting and hindering the protein quality control machinery. This review highlights the recent advances in phosphorylations regulating protein quality control, the impact in cardiac pathology, and the therapeutic opportunities presented by harnessing these modifications.